Gesture in poetry, movement and music: Approaching the total artwork through Sufism in Say I am You and Deniz Küstü (The Sea-Crossed Fisherman). Issue 3 (1st September 2016) - Ellison, Michael
In this article I speak about my experience of the connective thread of the gesture, and how metaphors of gesture across disciplines underpin relationships between music, poetry and dance. I explore the notion that, if there is a unifying force in the creation of Art and uncovering of Consciousness, it lies in some kind of Ur-gesture – a gesture that exists before translation into a certain medium – behind the forms a craftsman of music, dance or words of obligation 'reduces it' to. Further, I compare Rumi's ideas on sema to those behind Whitehouse's notion of Authentic Movement, and justify my approach to the staging of Rumi and sema in the opera Say I am You: as though the Mevlevi sema formal ritual had never been codified. Finally, I explore ideas surrounding Ur-gesture in interview with the foremost modern dance choreographer in Turkey today, Zeynep Tanbay, while probing her process of choreographing Deniz Küstü, my second opera.